2012
DOI: 10.15193/zntj/2012/83/122-135
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value and Technological Suitability of Milk Produced in Intensive and Traditional Systems in 3 Regions of Eastern Poland

Abstract: S t r e s z c z e n i eBadaniami objęto 68 gospodarstw zlokalizowanych w 3 rejonach wschodniej Polski, tzn. na nizinach (tereny nadbużańskie i biebrzańsko-narwiańskie), w Beskidzie Niskim i Bieszczadach, wyróżniając gospodarstwa produkujące mleko w systemie intensywnym i tradycyjnym. W 1589 próbach mleka oznaczono: zawartość tłuszczu, białka, kazeiny, laktozy i suchej masy, kwasowość (pH), stabilność cieplną, czas krzepnięcia mleka pod wpływem podpuszczki, zawartość α-laktoalbuminy, β-laktoglobuliny, albuminy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
4
6
0
Order By: Relevance
“…Organic milk coagulated faster and was therefore more suitable for cheese production. These findings are consistent with the results obtained by Barłowska et al [199] in conventional milk production. The authors indicated that green forage in the diet of cows reduced the rennet coagulation time.…”
Section: Technological Qualitysupporting
confidence: 94%
“…Organic milk coagulated faster and was therefore more suitable for cheese production. These findings are consistent with the results obtained by Barłowska et al [199] in conventional milk production. The authors indicated that green forage in the diet of cows reduced the rennet coagulation time.…”
Section: Technological Qualitysupporting
confidence: 94%
“…According to Barłowska et al (2012) the highest content of basic components was found in milk obtained from cows in the Beskid Niski region, which the authors explain by both the breed of cows and the greater diversity of botanical composition of pastures.…”
Section: Discussionmentioning
confidence: 99%
“…According to Barłowska et al (2012), in case of whey proteins, it was found that their content was higher in milk obtained from cows in mountainous regions, which the authors explain by both inter-breed differences and the botanical composition of the basic feed, which was green fodder from permanent greenlands suited to cultivation. Botanical and weight analyses of collected samples of pasture vegetation showed that in the Bieszczady and Beskid Niski regions there was a significantly higher proportion of herbs and weeds, compared to the lowland region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the specific character and difficult environmental conditions of mountain areas where food products are produced have been recognised by the European Commission for several years, by their introduction of the quality term 'mountain product' (Regulation EU 2012). Studies show that milk and dairy products produced in mountain areas are distinguished by their sensory profile, physicochemical parameters and, above all, higher content of health-promoting nutrients ( Zan et al 2006;Fedele 2008;Chion et al 2010;Barłowska et al 2012;Matras et al 2014;Rutkowska et al 2015). This is primarily due to the greater botanical diversity of pastures (Collomb et al 2002).…”
Section: Introductionmentioning
confidence: 99%